YÜKSEK ÖĞRETİM VE KALİTE YÖNETİMİ: GELİŞMEKTE OLAN ÜLKE BAĞLAMINDA BİR ARAŞTIRMA - TERTIARY EDUCATION AND MANAGEMENT OF QUALITY: A RESEARCH IN A DEVELOPING COUNTRY CONTEXT - Olcay Bektaş; Mehmet Eryılmaz; Ebru Aydoğan; Gülcan Petriçli; Duygu Acar Erdur; Esen Cimili Kara (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Tertiary education is accepted as one of the engines of economic growth at national level. However, as far as is known, there have been only a few research studies in literature on efforts to increase quality level of tertiary education institutions that have both an extensive data set and are based on the context of a developing country. Therefore, this study aims to examine the current situation of quality management efforts in Turkish tertiary education Institutions. The data for this study were collected from 672 units of 149 Turkish universities. According to the findings, more than half of the participating organizations did not have any quality management certificate, nor were they making any quality management efforts. Therefore, the findings indicated that there is still a very long and arduous way to be covered by Turkish tertiary education ınstitutions in spite of some important developments.